Technology-embedded health education on nutrition for middle-aged and older adults living in the community. (September 2019) - Chiu, Ching-Ju; Kuo, Su-E; Lin, Dai-Chan
Mobile technology provides young adults important support for self-directed learning, but whether there is related support for older adults is not clear. This study aims to determine whether 1) nutrition education combined with mobile technology-supported teaching improves knowledge of and self-efficacy for a healthy diet; 2) if adults who reported reviewing the electronic course material or searching health information online, showed significantly greater progress in knowledge of and self-efficacy for a healthy diet than did those who did not adopt the electronic support. A total of 35 middle-aged and older adults were recruited from the community. Enrollees who were unable to read, who participated in the course fewer than five times, who did not take the post-test, or who did not return complete questionnaires at the pre-test were excluded. Overall, 21 participants were finally analyzed, and 14 participated in the qualitative investigation. The study interventions included three traditional nutrition lectures and three touch-screen tablet computer lessons to access the Internet and nutrition applications. Structured and semi-structured questionnaires were used to collect both quantitative and qualitative data and record participants' Internet use conditions at home. Participants' nutrition knowledge significantly improved (meanpost-pre = 1.19, p = 0.001) and their self-efficacy about a healthy diet showed marginal improvement (meanpost-pre = 0.22, p = 0.07). Nutrition knowledge was positively correlated with their intensity of surfing the Internet ( r = 0.46, p < 0.05), or reviewing the electronic course material ( r = 0.48, p < 0.05) but not correlated with reviewing paper course material ( r = 0.19, p = 0.09). Qualitative results showed that participants reported feeling freshness, joyfulness, and great achievement because of the combined course material. Technology-supported learning combined with traditional health education might provide great opportunities for positive behavioral change, even in older adults without any previous Internet experience.